Effect of Predraft Ulnar Collateral Ligament Reconstruction on Future Performance in Professional Baseball: A Matched Cohort Comparison. Issue 6 (May 2018) - Camp, Christopher L.; Conte, Stan; D'Angelo, John; Fealy, Stephen A.; Ahmad, Christopher S.
Background: In recent years, there has been a dramatic rise in the annual number of ulnar collateral ligament (UCL) reconstructions performed in amateur baseball pitchers. Accordingly, increasing numbers of players are entering professional baseball having already undergone the procedure; however, the effect of prior UCL reconstruction on future success remains unknown. Purpose: (1) To provide an epidemiologic report on baseball players who undergo UCL reconstruction before being selected in the Major League Baseball (MLB) Draft, (2) to define the outcomes in terms of statistical performance, and (3) to compare these results with those of matched controls (ie, non–UCL reconstruction). Study Design: Cohort study; Level of evidence, 3. Methods: The MLB Amateur Draft Database was queried to identify all drafted pitchers who underwent UCL reconstruction before being drafted. For each pitcher drafted from 2005 to 2014 with prior UCL reconstruction, 3 healthy controls with no history of elbow surgery were randomly identified for matched analysis. A number of demographic and performance comparisons were made between these groups. Results: A total of 345 pitchers met inclusion criteria. The annual number of pitchers undergoing predraft UCL reconstructions rose steadily from 2005 to 2016 ( P < .001). For matched control analysis, 252 pitchers with a UCL reconstruction and a minimum 2-year follow-up (drafted between 2005 and 2014) were matched to 756 controls (non–UCL reconstruction). As compared with the non–UCL reconstruction group, pitchers who underwent predraft UCL reconstruction reached the MLB level with greater frequency (20% vs 12%, P = .003), and their MLB statistical performances were similar for all measures. Compared with all other pitchers drafted during that period, players who had a predraft UCL reconstruction demonstrated an increased likelihood of reaching progressive levels of play (Full Season A, AA, and MLB) within a given time frame ( P < .05 for all). Conclusion: The number of UCL reconstructions performed in amateur baseball players before the draft increased year over year for the entire study period. Professional pitchers who underwent UCL reconstruction as amateurs appear to perform at least as well as, if not better than, matched controls without elbow surgery.